Maximiser la représentativité de groupes dans un échantillonnage spatial - Estelle Kah; Michel Pruvot (Cybergeo)
The crucial problem of representativeness of a sample when realizing a survey, is considered through getting the best chances to avoid getting cases too close to the boundaries of other groups. Using an example of spatial sample of communes in the sub-regions of a department we present in a bunch of combined processes, a calculated example on a spreadsheet, and formulas to weight the random sampling.